PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BERBAGI PENGETAHUAN SECARA AKTIF TERHADAP PEMAHAMAN KONSEP MATEMATISSISWA KELAS VIII SMPN 23 PADANG - kaWahyu, Rahmati; Harisman, Yulyanti; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThe research is conducted due to great number of students who do not understand yet the concept of mathematics well, it is proven that there are still a lot of students who get low mark. This research is aimed at analyzing the learning activity of the students of class VIII SMPN 23 Padang and finding out whether the comprehension of the mathematical concept of the students by applying the strategy Active Knowledge Sharing is better than the comprehension of the mathematical concept of the students by conventional learning. This is an experimental research.The population of the research is the students of classVIII SMPN 23 Padang, academic year 2013/2014. The sample is taken at random. The instruments in this research are the observation sheet and the comprehension test of mathematical concept.The result of research shows that the activity of the students in learning mathematics using the strategy Active Knowledge Sharing increases. Hypothetical examination uses minitab by examining t, gained P-value = 0,000= 0,05, therefore it can concluded that the comprehension of the studentâs mathematical concept using strategy Active Knowledge Sharing is better than comprehension of the studentâs mathematical concept by conventional learning.